2022
DOI: 10.1186/s40900-022-00362-w
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on the involvement of adolescents and young adults (AYAs) with cancer during multiple research phases: “plan, structure, and discuss”

Abstract: Background Including the lived experience of patients in research is important to improve the quality and outcomes of cancer studies. It is challenging to include adolescents and young adults (AYAs) cancer patients in studies and this accounts even more for AYAs with an uncertain and/or poor prognosis (UPCP). Little is known about involving these AYAs in scientific research. However, by including their lived experiences during multiple phases of research, the quality of the study improves and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Adolescence and young adulthood are a period of transition from children to adults (Ferrari et al, 2021;Smith & Olsen, 2018). Adolescents and young adults are concerned about physical appearance and self-existence, construct their identity, develop body image and positive sexual identity, separate from their parents, develop their involvement with friends of the same age, date, and begin to make decisions and life choices (Broholm-Jørgensen et al, 2022;Ham et al, 2022).…”
Section: A B S T R a Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescence and young adulthood are a period of transition from children to adults (Ferrari et al, 2021;Smith & Olsen, 2018). Adolescents and young adults are concerned about physical appearance and self-existence, construct their identity, develop body image and positive sexual identity, separate from their parents, develop their involvement with friends of the same age, date, and begin to make decisions and life choices (Broholm-Jørgensen et al, 2022;Ham et al, 2022).…”
Section: A B S T R a Kmentioning
confidence: 99%
“…Adolescents and young adults diagnosed with cancer at an advanced stage will experience early death from cancer because there is no hope of recovery, but they do not face the threat of death immediately after diagnosis or after completing active cancer therapy (Ham et al, 2022). The poor quality of the post-care phase in adolescents and young adulthood is one of which is counseling on reproductive health .…”
Section: A B S T R a Kmentioning
confidence: 99%
“…However, the reporting of experiences with patient engagement in research with the AYA cancer patient population is very limited. In 2022, van Ham et al conducted semi-structured qualitative interviews with researchers (n = 9) and AYA cancer patients (n = 3) on experiences with patient engagement in research in Denmark [11]. The authors reported practical findings including an adjusted involvement matrix based on nine phases of research and five roles for patient research partners (PRPs).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported practical findings including an adjusted involvement matrix based on nine phases of research and five roles for patient research partners (PRPs). Implications include creating awareness of the value of patient engagement in research at the individual level, advocating for training AYAs and researchers in this respect, and at the institutional level, calling for structural changes to support this approach [11]. In 2023, Pappot reported experiences with patient engagement in research with a panel of 10-15 AYAs spanning multiple studies over 5 years at a cancer support facility in Finland [12].…”
Section: Introductionmentioning
confidence: 99%
“…Research into T/AYA clinical outcomes and experiences is challenging [13], even more so when seeking to directly capture the patient voice of those with advanced cancer due in part to unpredictable disease and symptom pattern and the increased psychological and emotional burden often seen in this cohort [14 ▪ ,15 ▪ ]. Small numbers mean studies tend not to focus on particular diagnostic groups.…”
Section: Introductionmentioning
confidence: 99%